Condensation heat transfer performance in multi-fluid compact heat exchangers with wavy and strip fins. (January 2022) - Vaisi, Ahmad; Javaherdeh, Kourosh; Moosavi, Rouhollah
Highlights: Condensation heat transfer performance of a compact HX with wavy fins is investigated. The thermal performance, Nu number, and f parameter were experimentally calculated. The optimum heat transfer surface ratio of the cross-direction flow is equal to 1. The two-phase flow pattern in the wavy fins of the middle HX is wavy and stratified. The TPF rises with higher height, length, and wave amplitude to wavelength ratio. Abstract: The effect of different geometrical parameters of wavy and strip fins in a three-fluid plate-fin compact heat exchanger on the condensation heat transfer in the middle heat exchanger has been experimentally investigated. The three-fluid heat exchanger consisted of three heat exchangers with strip and wavy fins. In the examined system, the hot and cold fluids flowed through the adjacent heat exchangers (strip channels), while the middle heat exchanger (wavy channels) was occupied with a single-component two-phase flow (condensed vapor). The Nusselt number, the friction factor, the heat transfer surface contribution between the middle heat exchanger and each of the adjacent heat exchangers, and the thermal performance factor were calculated using the measured data at the inlets and outlets of the heat exchangers, and by using the thermal balance equations between the fluids passing through the heat exchangers. In the examined heat exchanger, the hot and cold flows had a cross-direction with the two-phase fluid flow. The two-phase Reynolds number, the vapor quality, and the heat transfer surface contribution of the middle heat exchanger with the adjacent heat exchangers were 50–4800, 0.1–0.67, and 0.19–0.7, respectively. The results show that the two-phase flow pattern in the wavy channels of the middle heat exchanger is stratified and wavy. According to the findings, a higher thermal performance factor is observed when the ratio of the wavy channel heat transfer surface to the heat transfer surface of the cold or hot flows is closer to 1. Also, with higher wave amplitude to wavelength ratios, lower pitch to height ratio of the fins, the lower wavelength to the fin length ratios, and lower fin pitch to wave amplitude ratios are obtained a higher thermal performance factor. Graphical abstract: Image, graphical abstract